Identifying and Overcoming Mechanisms of PARP Inhibitor Resistance in Homologous Recombination Repair-Deficient and Repair-Proficient High Grade Serous Ovarian Cancer Cells - Gomez, Miriam K. (Cancers (Basel), 2020)
High grade serous ovarian cancer (HGSOC) is a major cause of female cancer mortality. The approval of poly (ADP-ribose) polymerase (PARP) inhibitors for clinical use has greatly improved treatment options for patients with homologous recombination repair (HRR)-deficient HGSOC, although the development of PARP inhibitor resistance in some patients is revealing limitations to outcome. A proportion of patients with HRR-proficient cancers also benefit from PARP inhibitor therapy. Our aim is to compare mechanisms of resistance to the PARP inhibitor olaparib in these two main molecular categories of HGSOC and investigate a way to overcome resistance that we considered particularly suited to a cancer like HGSOC, where there is a very high incidence of TP53 gene mutation, making HGSOC cells heavily reliant on the G2 checkpoint for repair of DNA damage and survival. We identified alterations in multiple factors involved in resistance to PARP inhibition in both HRR-proficient and -deficient cancers. The most frequent change was a major reduction in levels of poly (ADP-ribose) glycohydrolase (PARG), which would be expected to preserve a residual PARP1-initiated DNA damage response to DNA single-strand breaks. Other changes seen would be expected to boost levels of HRR of DNA double-strand breaks. Growth of all olaparib-resistant clones isolated could be controlled by WEE1 kinase inhibitor AZD1775, which inactivates the G2 checkpoint. Our work suggests that use of the WEE1 kinase inhibitor could be a realistic therapeutic option for patients that develop resistance to olaparib.